1993
DOI: 10.1002/eji.1830230905
|View full text |Cite
|
Sign up to set email alerts
|

In vitro induction of human cytotoxic T lymphocyte responses against peptides of mutant and wild‐type p53

Abstract: The central role of the p53 tumor suppressor gene product in oncogenesis is gradually being clarified. Point mutations in the p53 tumor suppressor gene are common in most human cancers and are often associated with p53 protein overexpression. Overexpressed wild-type or mutant determinants of the p53 protein thus represent an attractive target for immunotherapy of cancer directed against a structure involved in malignant transformation. An important step towards this goal is identification of epitopes of p53 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
127
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(147 citation statements)
references
References 54 publications
10
127
2
Order By: Relevance
“…In contrast, CD8 ϩ T cells recognizing peptide 261-269 of p53 had not been tolerized and displayed CTL activity after peptide immunization. Similarly, other investigators reported that CD8 ϩ and CD4 ϩ T cell lines generated from healthy humans contain self-p53 peptide-reactive T cells (38,39). Together with our study, these observations show that during thymic selection certain portions of selfp53 are well processed and presented (dominant-self) and induce CD4 and CD8 T cell tolerance.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, CD8 ϩ T cells recognizing peptide 261-269 of p53 had not been tolerized and displayed CTL activity after peptide immunization. Similarly, other investigators reported that CD8 ϩ and CD4 ϩ T cell lines generated from healthy humans contain self-p53 peptide-reactive T cells (38,39). Together with our study, these observations show that during thymic selection certain portions of selfp53 are well processed and presented (dominant-self) and induce CD4 and CD8 T cell tolerance.…”
Section: Discussionsupporting
confidence: 90%
“…The peptides were the HLA-A*0201-binding peptide STPPPGTRV, corresponding to WT p53 149-157 and LLGRNSFEV corresponding to WT p53 264-272 peptide, both representing wellestablished HLA-A*0201-restricted T cell epitopes. [18][19][20] The specificity of p53 tetramers used in this study was previously confirmed by competition of CD3 binding, staining against respective anti-p53-specific CTL lines and by the lack of staining with irrelevant CTL or HLA-A2 2 PBMC of healthy donors. [21][22][23][24] To minimize background staining, each tetramer was titered and used at the lowest concentration that still gave a clearly discernible positive population.…”
Section: Tetrameric Peptide-mhc Class I Complex (Tetramer) Assaysupporting
confidence: 62%
“…Several groups have been able to establish human CTL cultures from healthy HLA-A2 ϩ donors recognizing the epitope L9V spanning position 264 -272 of the p53 molecule, 11,13,22 and our group was the first to demonstrate killing of natural tumor cell targets by an in vitro established p53-specific CTL clone. 12 Subsequently, similar results were reported from a study by Gnjatic et al 13 describing the recognition of several natural tumor cell lines by an L9V-specific CTL line.…”
Section: Ctl Killing Of Natural Targetsmentioning
confidence: 96%